KEKUATAN HUKUM PERJANJIAN PENGIKATAN JUAL BELI PASCA DEVELOPER DIPAILITKAN - Fahmi, Muhammad; Janisriwati, Sylvia (LPPM STIH Awang Long, 2024)
The aim of this research is to provide an understanding regarding strong and weak binding Sale and Purchase Agreement deed in terms of buying and selling houses or land carried out by the community as buyers and developers as sellers. Especially when in his journey the developer is in trouble until it occurs that the developers are declared bankrupt and and all his wealth at that time and during the process of pailit will go into the bankrupt boedel. This type of research is normative law using legislative approaches. File on research is secondary data supported by primary and secondary legal materials and obtained from library studies, which are then analyzed by qualitative methods. As for the results of this study, Firstly, the sale and purchase binding agreement is an agreement between the developer and any person to carry out the sale and purchase of a house which can be carried out by the developer before the construction of the house which is made before a notary. Second, there are two deeds of Sale and Purchase Banding Agreement, namely a deed of sale and purchase agreement which has been paid off and Whika has not yet been paid off. If the status of the sale and purchase agreement has been paid in full and was made by a notary before the developer went bankrupt, then the status of the sale and purchase agreement is very strong. On the other hand, if the developer goes bankrupt with the buyer's status still in the installment phase, does not control the object and the sale and purchase agreement was not made by a notary, then the status is weak.